A linear benchmark between HYMAGYC, MEGA and ORB5 codes using the NLED-AUG test case to study Alfvénic modes driven by energetic particles. (1st October 2021) - Vlad, G.; Wang, X.; Vannini, F.; Briguglio, S.; Carlevaro, N.; Falessi, M. V.; Fogaccia, G.; Fusco, V.; Zonca, F.; Biancalani, A.; Bottino, A.; Hayward-Schneider, T.; et al.
Abstract: One of the major challenges in magnetic confinement thermonuclear fusion research concerns the confinement of the energetic particles (EPs) produced by fusion reactions and/or by additional heating systems. In such experiments, EPs can resonantly interact with the shear Alfvén waves. In the frame of the EUROfusion 2019–2020 Enabling Research project 'multi-scale energetic particle transport in fusion devices' (MET), a detailed benchmark activity has been undertaken among few of the state-of-the-art codes available to study the self-consistent interaction of an EP population with the shear Alfvén waves. In this paper linear studies of EP driven modes with toroidal mode number n = 1 will be presented, in real magnetic equilibria and in regimes of interest for the forthcoming generation devices (e.g. ITER, JT-60SA, DTT). The codes considered are HYMAGYC, MEGA, and ORB5, the first two being hybrid MHD-gyrokinetic codes (bulk plasma is represented by MHD equations, while the EP species is treated using the gyrokinetic formalism), the third being a global electromagnetic gyrokinetic code. The so-called NLED-AUG reference case has been considered, both for the peaked on-axis and peaked off-axis EP density profile cases, using its shaped cross section version. Comparison of the spatial mode structure, growth rate and real frequency of the modes observed will be considered in detail. The dependence of mode characteristics when several parameters are varied, as, e.g. the ratio between EP and bulk ion density and EP temperature, will be presented. A remarkable agreement is observed among the three codes for the peaked off-axis case, obtaining all of them a TAE localized close to the magnetic axis. On the other hand, some differences are observed when considering the peaked on-axis case, where two modes are observed (a TAE localized in the radial external region, and an RSAE around mid-radius). A careful analysis of the stability of this equilibrium, in particular by varying self-consistently the EP drive, will allow to reconcile the results of the three codes.